Há lugar para uma “racionalidade científica” no pensamento de Paul Feyerabend? - Flach, Miguel Ângelo (Universidade do Vale do Rio dos Sinos, 2012)
The aim of this dissertation is to investigate whether there is room for “scientific rationality” in the writings of Paul Feyerabend and, if so, in what terms this concept is expressed. My starting point is Feyerabend’s radical critique of the traditional view of rationality and rationalism. First of all, I examine the full meaning of the concept of “rationalism” which he proposes. In Chapter 1, the context of ancient Greek culture is analysed, since it is within this context that he identifies an incipient abstract rational thought which permeates the origins of philosophy, and which coincides with the ascent of rationalism as a transformer of “Reason” in terms of the source of a given privileged tradition. According to Feyerabend, the excessive belief in the power of “Reason” which began in antiquity is also present in the essence of the modern rationalism of Popper and Lakatos, and Chapter 2 examines the theoretical and epistemological premises of this in the light of Feyerabend’s approach to scientific praxis. In this way, the internal implosion of the view of rationalism criticised takes shape, and it is by means of this strategy that the relevance of Feyerabend’s critique is assessed. Through an analysis of the principal writings of Popper and Lakatos it is my intention to avoid any conditioning which may result from the content of this critique. Chapter 3 analyses Feyerabend’s philosophy and the changes and transformations in his writings in order to verify if there is indeed room for the notion of “scientific rationality”. The terms of these changes are subjected to a more rigorous study so that his mature concept of “scientific rationality” can be clarified. The conclusion I draw is that it is, in fact, possible to identify such a concept, but that this is in opposition to Popper’s view of scientific rationality as something universal, absolute and intrinsic to the aims of scientific knowledge. From the scientific praxis point of view adopted by Feyerabend, this rationality is historicized and contextualized; it is active, open and dynamic.
Keywords: Racionalismo; Razão; Práxis científica; Racionalidade científica; Rationalism; Reason; Scientific praxis; Scientific rationality; ACCNPQ::Ciências Humanas::Filosofia